Mg(OH)2 Nanorods Synthesized by A Facile Hydrothermal Method in the Presence of CTAB - Dhaouadi, Hassouna; Chaabane, Hedia; Touati, Fathi (Nano-Micro Letters, 2011)
Magnesium hydroxide (Mg(OH)2) nanorods were synthesized by a simple and facile hydrothermal method in the presence of cetyltetramethylammonium bromide (CTAB) as a surfactant. Nanorods of magnesium oxide MgOwere also induced by thermal decomposition of Mg(OH)2 nanorods at 700°C, By using disk diffusion technique, the Mg(OH)2 nanorods were found to exhibit higher antibacterial efficiency against several tested bacterial strains.